The Nature whence Spirit came: on Adrian Johnston’s Hegelianism - Tupinambá, Gabriel (Stasis, 2016)
Book review: Adrian Johnston, Prolegomena to Any Future Materialism. Vol. I. The Outcome of Contemporary French PhilosophyEvanston, IL: Northwestern University Press, 2013, 257pp., ISBN 978-0810129122Adrian Johnston, Adventures in Transcendental Materialism. Dialogues with Contemporary ThinkersEdinburgh: Edinburgh University Press, 2014, 376pp., ISBN 978-0748673285